Single nucleotide variant discovery of highly inbred Leghorn and Fayoumi chicken breeds using pooled whole genome resequencing data reveals insights into phenotype differences. (December 2016) - Fleming, D.; Koltes, J.; Fritz-Waters, E.; Rothschild, M.; Schmidt, C.; Ashwell, C.; Persia, M.; Reecy, J.; Lamont, S.
Abstract Background Analyses of sequence variants of two distinct and highly inbred chicken lines allowed characterization of genomic variation that may be associated with phenotypic differences between breeds. These lines were the Leghorn, the major contributing breed to commercial white-egg production lines, and the Fayoumi, representative of an outbred indigenous and robust breed. Unique within- and between-line genetic diversity was used to define the genetic differences of the two breeds through the use of variant discovery and functional annotation. Results Downstream fixation test (F ST ) analysis and subsequent gene ontology (GO) enrichment analysis elucidated major differences between the two lines. The genes with highF ST values for both breeds were used to identify enriched gene ontology terms. Over-enriched GO annotations were uncovered for functions indicative of breed-related traits of pathogen resistance and reproductive ability for Fayoumi and Leghorn, respectively. Conclusions Variant analysis elucidated GO functions indicative of breed-predominant phenotypes related to genomic variation in the lines, showing a possible link between the genetic variants and breed traits.